(untitled) (REMUNOM, 2023)
This article aimed to verify the constitutionality of the military crime of publication or undue criticism, provided for in art. 166, of the Military Penal Code, against the freedom of expression and thought of the military. To achieve the objective, the method used was bibliographical and documentary research and data collection with the PMMG. For the development of the work, we sought to know the theories that deal with constitutional principles, more precisely freedom of expression, hierarchy and discipline, as well as the possibility of conflicts and limitations suffered by each of these principles. Thus, a valid legal path was sought to balance the performance of each one of them and maintain the harmony of the legal system, allowing the military police to fully use their right to freedom of expression, without, however, incurring in acts that offend deliberate manner the hierarchy and discipline that are considered the pillars of the Military Institutions. The study also evaluated the impact of this crime on the Military Police of Minas Gerais, with the analysis of information from the Internal Affairs of the Military Police, as well as some practical cases that better elucidated the theoretical content initially presented. Thus, it was found that the crime highlighted lacks constitutionality.